Multimedia w bibliotece jako środek aktywizowaniaosób z uszkodzonym słuchem = Multimedia in the library as a means of activating people withhearing impairments - Woźniczka-Paruzel, Bronisława (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article is devoted to various multimedia forms that can be used in libraries when working with deaf or hard-of-hearing users. After some terminological and methodological observations, the article discusses problems of the deaf community connected with communication and culture, and barriers to accessing reading and written information resulting from hearing damage, when these are issued traditionally. Against this background, new technologies and computer programs that enable the breaking down of communication barriers (i.e. online translators of sign language and translation systems) are presented. The next part of the discussionis focused on multimedia reading materials for deaf children: on fairy tales andreading (with translations into sign language, recorded in this language or constituting visual transcriptions of literary texts). Multimedia for deaf youth (films with actors using sign language, music videos with musical hits, where texts have been translated into sign language, and sign-language poetry) are also presented. The next part of the article describes the Internet TV for the deaf, thanks to whichit is possible to access information from the country and the world, and, lastly, interactive multimedia programs for children and youth with hearing loss, which stimulate dysfunctional functions, encouraging reading and preparing for reading.The whole article finishes with attempts to indicate how to encourage people with hearing impairments to use the library, and how to motivate them.
Keywords: multimedia; biblioteka; Osoby niesłyszące i niedosłyszące; bariery komunikacyjne; Deaf and hard-of-hearing people; communication barriers; Sign language; library